Financial Literacy for Smallholder Sheep Fattening Farmers - Ephrem, Nahom; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2021)
The International Center for Agricultural Research in Dry Areas, in close cooperation with regional agricultural research institutes and partners, implements improved sheep fattening methods and technologies in Ethiopia. The project aims to improve the income of rural farmers from sheep fattening. Sheep farming is one of the lucrative commercial businesses in Ethiopia. With basic knowledge of sheep husbandry and management, farmers and young people in Ethiopia can be successful in sheep fattening and generate good income from the sector. Young people from rural areas who are unemployed or have little land ownership are getting involved in sheep farming. From an economic point of view, farmers seek a balance between production levels and economic outcomes of their livestock systems. However, farmers have made minimal progress towards commercial fattening with clear production goals and financial means. The factors necessary for development of entrepreneurship, such as risk-taking, access to easy finance and coordination between factors of production, are limited. Financial literacy can provide farmers with the knowledge and skills they need to successfully set financial goals, plan and manage their money, as well as build their wealth. These skills will help them manage their daily expenses, expand their entrepreneurial opportunities, and reduce their overall vulnerability. This financial literacy manual has been adapted as a guide for community and development trainers for members of farmer groups involved in sheep production. It is designed to impart basic knowledge, skills, attitudes, and practices for personal and cooperative money management.